2015
DOI: 10.1007/s00122-015-2478-0
|View full text |Cite
|
Sign up to set email alerts
|

New QTL alleles for quality-related traits in spring wheat revealed by RIL population derived from supernumerary × non-supernumerary spikelet genotypes

Abstract: A population developed from an exotic line with supernumerary spikelets was genetically dissected for eight quality traits, discovering new genes/alleles with potential use in wheat breeding programs. Identifying new QTLs and alleles in exotic germplasm is paramount for further improvement of quality traits in wheat. In the present study, an RIL population developed from a cross of an elite wheat line (WCB414) and an exotic genotype with supernumerary spikelets (SS) was used to identify QTLs and new alleles fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
49
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 48 publications
(58 citation statements)
references
References 63 publications
9
49
0
Order By: Relevance
“…In contrast to our results, Tsilo et al (2011) and Prashant et al (2015) found high broad-sense heritability for most of the end-use quality traits in wheat. Similarly, the current study, Echeverry-Solarte et al (2015) reported very high broad-sense heritability for flour extraction and MMLPT.…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…In contrast to our results, Tsilo et al (2011) and Prashant et al (2015) found high broad-sense heritability for most of the end-use quality traits in wheat. Similarly, the current study, Echeverry-Solarte et al (2015) reported very high broad-sense heritability for flour extraction and MMLPT.…”
Section: Discussionsupporting
confidence: 80%
“…Performing these evaluations at a late stage in the breeding program often results in ostensibly promising wheat lines with high yield and resistance to diseases that cannot be released due to poor end-use quality traits, such as a weak performance for milling parameters and baking properties. To address these challenges, many studies have been conducted to identify quantitative trait loci (QTL) and associated markers for end-use quality traits, with the aim to use such markers in marker-assisted selection (MAS) to improve quality traits in early generations of the breeding program (Campbell et al 2001; Groos et al 2003; Prasad et al 2003; Breseghello et al 2005; Kulwal et al 2005; Arbelbide and Bernardo 2006; Breseghello and Sorrells 2006; Huang et al 2006; Kuchel et al 2006; Kunert et al 2007; Mann et al 2009; Tsilo et al 2010; Zhao et al 2010; Carter et al 2012; Li et al 2012a; Simons et al 2012; El-Feki et al 2013; Mergoum et al 2013; Deng et al 2015; Echeverry-Solarte et al 2015; Tiwari et al 2016; Jin et al 2016). It should be mentioned that MAS for end-use quality traits would be commenced from F 5 generation onwards if a single seed decent (SSD) method is used to develop wheat cultivars.…”
Section: Introductionmentioning
confidence: 99%
“…Numerous studies have identified associations between HMW and LMW glutenin subunits and wheat quality (Payne 1987;Perretant et al 2000;Sourdille et al 2003;McCartney et al 2006;Nelson et al 2006;Zhang et al 2008;Li et al 2009;Mann et al 2009;Suprayogi et al 2009;Reif et al 2011;Li et al 2012;Echeverry-Solarte et al 2015). In this study, KN9204 and J411 differed at two HMW glutenin loci (Glu-A1 and Glu-B1) and two LMW glutenin loci (Glu-A3 and Glu-B3).…”
Section: Novel Stable Qtls and Qtl Co-segregation With Known Genesmentioning
confidence: 72%
“…However, an increase in yield often results in a decrease in kernel quality parameters, such as a lower grain protein content (GPC), because of a dilution effect (Suprayogi et al 2009). Notably, previous studies have shown that quantitative trait loci (QTLs) for yield are not always negatively correlated with quality (Sourdille et al 2003;Huang et al 2006;Kunert et al 2007;Echeverry-Solarte et al 2015). Therefore, knowledge of the genetic basis of kernel size and its correlation with quality is valuable for the genetic improvement of both yield and quality.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation